2016
DOI: 10.15671/hjbc.20164420579
|View full text |Cite
|
Sign up to set email alerts
|

Horseradish Peroxidase Immobilized into Organogel-Silica Composite for Transformation of Chlorophenols to Biodegradable Organic Acids

Abstract: F enol ve türevleri tehlikeli çevresel atıklardır ve bu nedenle çevreden uzaklaştırılmaları gerekir. Klorofenollerin enzimatik oksidasyonu uygun bir seçenek olarak düşünülür ama fenolik bileşiklerin polimerizasyonu nedeniyle çökmesine yol açar ve kontamine suların güvenli bir şekilde atılması yönünde flokülasyonun ek bir adımını gerektirir. Bu çalışmada, setiltrimetilamonyum bromür ters mikroemülsiyon ile mikroemülsiyon organojel ve jelatin hazırlandı ve yaban turpu peroksidazı (HRP, E.C.1.11.1.7) için immobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Previous study also indicated that T. versicolor has 88% decolorization rate at 100 rpm with 4 days incubation [22] Schizosaccharomyces pombe, Kluyveromyces marxianus, Candida sp., C. tropicalis, C. lipolytica, C. utilis, C. quilliermendii and C. membranaefaciens. In another study on Funalia trogii by Yesilada et al [23,24] showed that the highest decolorization rate for Astrazon Red FBL dye was obtained at 100-150 rpm. In our study, results are showed that decolorization process do not affect from agitation speed.…”
Section: Discussionmentioning
confidence: 94%
“…Previous study also indicated that T. versicolor has 88% decolorization rate at 100 rpm with 4 days incubation [22] Schizosaccharomyces pombe, Kluyveromyces marxianus, Candida sp., C. tropicalis, C. lipolytica, C. utilis, C. quilliermendii and C. membranaefaciens. In another study on Funalia trogii by Yesilada et al [23,24] showed that the highest decolorization rate for Astrazon Red FBL dye was obtained at 100-150 rpm. In our study, results are showed that decolorization process do not affect from agitation speed.…”
Section: Discussionmentioning
confidence: 94%
“…Size distribution analysis of BZD-free and BZD-loaded μE of all formulations was performed to check the stability of the dispersed partciles using dynamic light scattering (DLS) (Khan et al, 2016). As shown in Figure 4, the particle size of BZD-free μE droplet was 26.3 ± 1.4, 45.3 ± 2.8 and 36.5 ± 1.8 nm for formulation A, B and C, respectively each represented monostructured droplets by a single peak (Soomro et al, 2016). When BZD was loaded into the μE, the average partcile size increased to 36.2 ± 2.5, 53.5 ± 2.5 and 58.2 ± 2.3 nm for formulation A, B and C respectively, indicating the accumulation and encapsulation of BZD inside the interfacial layers of microstructres (Richard et al, 2017;Xiang et al, 2023).…”
Section: Size Distribution Analysismentioning
confidence: 99%